On the reversible quadratic polynomial vector fields on S-2 - Pereira, Weber F. [UNESP]; Pessoa, Claudio [UNESP] (Academic Press Inc. Elsevier B.V., 2012)
We study a class of quadratic reversible polynomial vector fields on 52 with (3, 2)-type reversibility. We classify all isolated singularities and we prove the nonexistence of limit cycles for this class. Our study provides tools to determine the phase portrait for these vector fields. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Reversible polynomial vector fields; Centers; Limit cycles; Phase portrait